"DIGITAL TRUST: Bagaimana Rating dan Review Membentuk Keputusan Pembelian Fashion Online di Era Gen Z" - Hermawan Budiyanto; Mochamad Novian (CiDEA Journal, 2025)
The rapid advancement of information and communication technology has positioned e-commerce as a primary shopping channel, with Shopee emerging as the most popular platform in Indonesia. In the context of online fashion purchases, consumers face inherent limitations due to the inability to physically inspect or try products. Consequently, product ratings and reviews function as critical forms of social proof, helping to reduce uncertainty and perceived purchasing risk. This study investigates the influence of product ratings and reviews on purchasing decisions for fashion products on Shopee, focusing on undergraduate students at Universitas 17 Agustus 1945 Semarang. Employing an associative quantitative approach, data were collected through a closed-ended questionnaire distributed to 100 purposively selected respondents who had purchased fashion products on Shopee within the last three months. The independent variables are product ratings and product reviews, while the dependent variable is the consumer purchasing decision. Statistical analyses include validity and reliability testing, correlation analysis, t-tests, F-tests, and the coefficient of determination. The study’s findings are expected to offer both practical insights for e-commerce businesses in developing effective digital communication strategies and theoretical contributions to the understanding of digital consumer behavior in the e-commerce environment.